Main karstic landscapes and caves of Costa Rica - Ulloa Carmiol, Andrés (2024)
Several carbonate rocks present in the geological record of Costa Rica host the karst landscapes of the country. Up to 450 caves have been reported, of which 74% occur in carbonate rocks. This paper presents updated information on the main karstic areas of Costa Rica, with exhaustive information on four karst landscapes located in Tempisque, Zona Sur, Venado of San Carlos, and Limón. Tempisque karstlands host the Barra Honda National Park, the only National Park intended for cave and karst protection in the country. This park exhibits several caves (mostly with vertical passages) and surface karst expressions such as dolines, mogotes, travertine cascades, and karren fields. The Terciopelo cave and the Cuevita are the only ones used for touristic activity. Zona Sur contains the most extensive karstic landscape in the country, with carbonate rock outcrops of about 100 km along Fila Costeña. This area is developed mainly in highly tectonized Eocene limestone. Furthermore, Zona Sur contains the most remarkable dolines in the country and several sinking streams that connect with cave systems. The Corredor River basin includes a cave system of almost 3 km long of surveyed passages. Another important karstic area is Venado of San Carlos, which hosts a karst landscape developed in Miocene carbonate rocks. This region is tectonically affected by Venado Transtensive System, which is a fault system that limits the limestone outcrops, and influences cave patterns. Limestone is overlain by younger volcanic deposits, making superficial karstic expression not very evident. Nevertheless, this area hosts the most extensive cave system known in the country, which consists of three caves that in total have almost 5 km of surveyed passages. Finally, Limón karstlands occur in Pliocene–Pleistocene reef-carbonate rocks in a seismically active area. A LiDAR survey in Limón revealed hundreds of dolines and conical karst as the most remarkable surface karst expressions.